2012
DOI: 10.4103/0971-4065.97117
|View full text |Cite
|
Sign up to set email alerts
|

Renal disease in human immunodeficiency virus - Not just HIV-associated nephropathy

Abstract: The aim of the study was to determine the various histopathological lesions in human immunodeficiency virus (HIV) patients with renal dysfunction and to establish clinicopathological correlation. Over a period of two years from January 2008 to March 2010, 27 HIV positive patients with renal dysfunction were subjected to renal biopsy. Of the 27 patients, 23 were males and four were females (85.2% males, 14.8% females). Mean age was 38.2 ± 10.36 (range 20 – 60) years. The probable mode of acquisition of HIV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
6
6
0
Order By: Relevance
“…Furthermore, of the 27 patients diagnosed with HIVAN on renal biopsy in a study in South Africa, only 3 were on ART [ 17 ]. This reaffirms the importance of renal biopsy in accurately diagnosing renal disease, particularly HIVAN [ 12 , 17 , 48 ], so that ART can be initiated early to improve outcomes. Sadly, due to a lack of resources and specialists, access to renal biopsy is limited to urban tertiary hospitals in South Africa.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Furthermore, of the 27 patients diagnosed with HIVAN on renal biopsy in a study in South Africa, only 3 were on ART [ 17 ]. This reaffirms the importance of renal biopsy in accurately diagnosing renal disease, particularly HIVAN [ 12 , 17 , 48 ], so that ART can be initiated early to improve outcomes. Sadly, due to a lack of resources and specialists, access to renal biopsy is limited to urban tertiary hospitals in South Africa.…”
Section: Discussionsupporting
confidence: 53%
“…In the current review, HIVAN was the most common histology seen on renal biopsy [ 15 , 31 ]. Other histologies have been documented in various studies both locally [ 12 , 17 , 22 , 31 ] and overseas [ 48 ]. The third leading cause of end stage renal disease (ESRD) in African Americans aged between 20 and 64 years was found to be HIVAN [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kidney biopsy series in HIV patients from India, have reported wide variability in prevalence of HIVAN, ranging from 0% to 85% [Table 3]. [89101112133435] These widely variable results emphasize limitations on drawing conclusions from single-center studies with small sample sizes. Therefore, we did a systemic review of literature on kidney biopsy in adult HIV patients from India.…”
Section: Discussionmentioning
confidence: 99%
“…While HIVAN has been reported consistently in Western studies, the prevalence in studies from Asia has been found to low/absent. [78] The available studies from India differ strikingly, with some studies showing presence of HIVAN,[91011] whereas others reporting complete absence of this entity. [81213] With this perspective, the present study was carried out to elucidate the histological spectrum of renal disease in HIV patients from a tertiary care center from India.…”
Section: Introductionmentioning
confidence: 99%
“…India faces the threat of an AIDS epidemic; nevertheless risk factors and the racial background of our HIV positive population are different from those in the western countries (1). As studies pertaining to renal diseases in HIV and data on their histopathological lesions from India are limited, (4,5) this study was conducted to document the clinicopathological features of various renal diseases in an HIV-positive patient population in a south Indian tertiary care center.…”
Section: Introductionmentioning
confidence: 99%